Optimizing linkage to care and initiation and retention on treatment of adolescents with newly diagnosed HIV infection. (1st July 2017) - Ruria, Eva Caroline; Masaba, Rose; Kose, Judith; Woelk, Godfrey; Mwangi, Eliud; Matu, Lucy; Ng'eno, Hillary; Bikeri, Beatrice; Rakhmanina, Natella
Abstract : Objective: Unsuccessful linkage to care and treatment increases adolescent HIV-related morbidity and mortality. This study evaluated the effect of a novel adolescent and youth Red Carpet Program (RCP) on the timing and outcomes of linkage to care. Design: A prepost implementation evaluation of the pilot RCP program. Settings: Healthcare facilities (HCFs) and schools in Homa Bay County, Kenya. Study participants: HIV-infected adolescents (15–19 years) and youth (20–21 years). Interventions: RCP provided fast-track peer-navigated services, peer counseling, and psychosocial support at HCFs and schools in six Homa Bay subcounties in 2016. RCP training and sensitization was implemented in 50 HCFs and 25 boarding schools. Main outcome measures: New adolescent and youth HIV diagnosis, linkage to and retention in care and treatment. Results: Within 6 months of program rollout, 559 adolescents and youths (481 women; 78 men) were newly diagnosed with HIV (15–19 years n  = 277; 20–21 years, n  = 282). The majority ( n  = 544; 97.3%) were linked to care, compared to 56.5% at preimplementation ( P  < 0.001). All (100.0%; n  = 559) adolescents and youths received peer counseling and psychosocial support, and the majority ( n  = 430; 79.0%) were initiated on treatment. Compared to preimplementation, the proportion of adolescents and youths who were retained on treatment increased from 66.0 to 90.0% at 3 months ( P  < 0.001), and from 54.4 to 98.6% at 6 months ( P  < 0.001). Conclusion: Implementation of RCP was associated with significant improvement in linkage to and early retention in care among adolescent and youth. The ongoing study will fully assess the efficacy of this linkage-to-care approach.